1979
DOI: 10.1055/s-0028-1092713
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Maturation Patterns of Serum Corticosterone and Growth Hormone in Rats: Effect of Chronic Thyroxine Administration

Abstract: The effects of chronic neonatal hyperthyroidism in rats on the ontogenic pattern of serum corticosterone and growth hormone (GH) were studied. Thyroxine (T4) treated and saline injected rat pups were sacrificed under basal and stress conditions. In comparison to saline control animals, daily T4 administration (0.4 micrograms/gram body weight) produced a sustained elevation in basal corticosterone levels by day 12 and a significant elevation of serum corticosterone in response to stress by day 4. The serum GH l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Thus, neonatal Tj administration re sults in an early increase in basal corticosterone titers and CBG levels [6,10,22] as well as in the early maturation of the adrenocortical response to stress [29]. In contrast, PTU administration during this period delays the maturation of the adrenocortical stress response and suppresses CRF-like activity in the hypothalamus [23,24].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, neonatal Tj administration re sults in an early increase in basal corticosterone titers and CBG levels [6,10,22] as well as in the early maturation of the adrenocortical response to stress [29]. In contrast, PTU administration during this period delays the maturation of the adrenocortical stress response and suppresses CRF-like activity in the hypothalamus [23,24].…”
Section: Discussionmentioning
confidence: 98%
“…Plasma ACTH levels are increased in neo-T4 rats with respect to controls at 12 days of life (table III) which could be an effect of the administration of thyroxine until the 8th day of life, considering that the chronic adminis tration of this hormone induces an increase in plasma corticosterone [26], In cortisoltreated animals, ACTH is decreased since the 8th day of life. This explains why authors [10,11,29] found a decrease in response to ether at 23 days of life in control-treated rats be cause they compared the response to normal rats treated with ether and not to the basal levels in the former groups.…”
Section: Discussionmentioning
confidence: 99%
“…This impairment could be related to the major disturbance of carbohydrate metabolism of neo-T4 rats in the neonatal period, with low liver glycogen, blood glucose and insulin levels, which implies a lack of energy substrates for the neonatal brain (Escrivá & Pascual-Leone 1981;Dickerman et al 1969). On the other hand these alterations in pituitary GH content could be a consequence of treatment with thyroid hormones, since chronic neonatal hyper¬ thyroidism, though produced by much smaller doses of T4, has been shown to alter the develop¬ mental pattern of serum GH (Poland et al 1979).…”
Section: Discussionmentioning
confidence: 98%